TRAINING IN MAKING AVOCADO LEAF TEA AND APPROPRIATE OVITRAP TECHNOLOGY AS A PREVENTIVE MEASURE FOR HYPERTENSION AND DENGUE HEMORRHAGIC FEVER (DHF) IN SANGKRAH VILLAGE, SURAKARTA - Dewi Puspito Sari; Fiqi Nurbaya; Nine Elissa Maharani; Titik Haryanti; Annisa Dewi Suryaningsih; Desti Pramudika Romadhoni (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Indonesia is still burdened with increasing hypertension and Dengue Hemorrhagic Fever (DHF). prevention of hypertension and DHF is needed. Sangkrah Surakarta Sub-District is an area where some of the people pay less attention to health conditions and environmental hygiene, thus triggering an increase in the number of more serious stroke cases. It is necessary to take steps to control hypertension, stroke and DHF that are easy and can be carried out. Objective: To increase partners' knowledge and skills through training in making ovitrap and avocado leaves as a preventive measure for hypertension, stroke and dengue. Method: This community service partner is the PKK Women's Group in RT 01 RW 13, Sangkrah Village, Surakarta, with a total of 20 people. This community service activity begins with identifying the needs of partners, preparing and permitting, counseling on hypertension, stroke and DHF, training on avocado leaves and making ovitrap, evaluating the implementation and sustainability of activities. At the counseling stage to measure the understanding of partners the service team distributed pretest and posttest questionnaires with the aim of whether there was an increase in partners' understanding. Results: The results of outreach activities for partners experienced an increase in participants' understanding of 23.45%, partners were able to make avocado and ovitrap tea during community service activities. Conclusion: Partners are very enthusiastic about participating in the counseling and training program, this is realized through increasing partners' understanding of efforts to prevent hypertension, stroke and DHF and being able to independently produce avocado and ovitrap leaves. Keywords: Avocado Leaf Tea, Ovitrap, Stroke, DHF, Sangkrah